Link between Motor Competence and Health Related Fitness in Children and Adolescents - Luz, Carlos (2022)
This study examined motor competence (MC) behavior in 6- to 14-year-old children, and investigated the differences in health-related fitness (HRF) between high and low MC groups, according to sex and age. A sample of 564 children (288 males) participated in this study, divided into three age groups (6?8 years; 9?11 years; 12?14 years). Total MC and its three components (stability, locomotor, and manipulative) were assessed with a quantitative instrument. HRF was evaluated using a maximal multistage 20-m shuttle-run test and the handgrip test. Participants were divided into tertiles according to their MC level and high and low MC groups were analyzed. Overall, MC increased across age groups for both sexes, but boys presented better results than girls. The high MC group outperformed their low MC peers in all HRF variables, independent of their age group. Although cardiovascular fitness increased with age for both the high and low MC groups, the differences between these groups were greater in older children compared to younger children, within the study age range. The findings suggest that MC interventions should be considered as an important strategy to enhance HRF, and girls at a young age should be a priority target.